ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. H DI WILAYAH KERJA PUSKESMAS KUIN RAYA KECAMATAN BANJARMASIN BARAT - Nur Cahyani Ari Lestari; Adinda Raudita; Muflihah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
PWS-KIA recapitulation data at the Kuin Raya Health Center in 2020 total coverage of pure K1 is 356 people (93.9%), K4 352 people (92.8%). Delivery by health workers 349 with (96.4%). Postpartum services were 419 people (76.3%). KN1 as many as 551 infants (100%) and complete KN as many as 448 infants (81.3%).Research method used in the preparation of the final report is descriptive research with case study method. The research was conducted at Sungai Jingah Health Center Banjarmasin Barat, and took place from October 2020 - January 2021. The subject used in this case study with midwifery care management was Mrs. H G2P0A0 35 weeks pregnant which was given comprehensively from pregnancy, childbirth, postpartum, newborn and family planning in the Kuin Raya Health Center Banjarmasin Work Area. On the results of the Final Project Report (LTA) with Comprehensive Midwifery Care carried out from pregnancy, childbirth, postpartum, newborn and family: Subjective and objective data on care for pregnancy, childbirth, newborns, postpartum and family planning on Ny. H has been collected. Subjective and objective data on the care of pregnancy, childbirth, newborns, postpartum and family planning on Ny. H has been interpreted. Based on subjective and objective data on care of pregnancy, childbirth, newborns, postpartum and family planning on Ny. H can be drawn assessment or diagnosis in all care is physiological. Based on the data analysis, there is no need for immediate action for collaboration and referral to care for pregnancy, childbirth, newborns, postpartum and family planning in Ny. H.